The role of authoritative parenting and self-regulation in controlling adolescent aggressiveness - Abdillah, Muhamad Hasan; Zurqoni, Zurqoni; Saugi, Wildan; Sutoko, Ibnu (International Journal of Evaluation and Research in Education (IJERE), 2025)
Seeing the many cases of adolescent violence that occurred in Yogyakarta, Indonesia, this study was interested in examining the suitability of authoritative parenting and self-regulation abilities to the level of adolescent aggressiveness. The subjects of this study were 154 class XII students of State Senior High School 1 Sleman. The sample selection was obtained using a stratified random sampling technique. The aim is to obtain student representation from each class. Researchers use the scale as the main tool in obtaining research data on aggressiveness, authoritative parenting and self-regulation. The data was then analyzed using multiple linear regression with the SPSS V26 program. The results of the analysis showed that, simultaneously, authoritative parenting and self-regulation were very significant in suppressing the emergence of aggressiveness in adolescents (F=51.76 and Sig.=.000). Then, both authoritative parenting (Beta=-.37 with Sig.=.000) and self-regulation (Beta=-.35 with Sig.=.000) both were able to have a significant effect on adolescent aggressiveness partially. The conclusion is that adolescents need authoritative parenting at this phase; this is necessary to avoid the emergence or development of aggressiveness in adolescents. Besides that, adolescents must also be equipped with self-regulation skills because most activities are carried out without parental supervision.